ANALYSIS OF LIQUID VISCOSITY VALUE USING FALLING BALL METHOD USING DIGITAL IMAGE TECHNOLOGY BASED ON LONG EXPOSURE FEATURES - Noke Kesaulya; Abdul Haji Amahoru; Maria A Hertiavi (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
Physics is the science that studies natural phenomena which observation is one of the most important aspect. Observations were made to study the physical phenomena and, if necessary, measurements can be made using appropriate, easily accessible as well as sophisticated devices. In this study, observation and measurement of a straight motion in a viscometer tube device has been developed. The device is also able to measure viscosity of the liquid (indirectly) using the falling ball method by means of Long Exposure technique. The viscosity of a liquid is essentialy related to drag force that caused by friction between the liquid molecules, which are able to resist fluid flow. Long Exposure is a technique of image acquisition which can preserve information about traces of objects moving at a certain time that might not be able to be captured with the naked eye. The falling ball method is based on a measurement of terminal velocity of the falling ball in a viscous liquid. In the experiments, lightmeter is a solid ball with varying sizes coated with phosphorus paint which was released from the surface of the liquid (glycerin and honey) inside a cylindrical tube. A camera with long exposure feature is placed in front of a perforated disk that serves as a chopper, which are essentially slits for the camera to capture the trajectory of the ball and convert the continuous trace into discrete traces. Using a simple digital image processing and digital image analysis techniques, the traces of the trajectory of the ball can be analyzed and thus we can obtain the data of the position for each time interval, thus the speed of the ball can be observed and the type of the motion can be analyzed (accelerated and motion with constant velocity). The calculated liquid viscosity is 0.7885 Pa.s viscosity with error 6.55% for glycerin, and as for honey the viscosity is 3.9162 Pa.s with precision of 99.98%. It can be concluded that these devices can be used to observe the phenomenon of straight motion with constant velocity and accelerated motion in viscosity tube, determines the value of the viscosity of a liquid with a good accuracy and precision